Whole genome sequencing: A new paradigm in the surveillance and control of human tuberculosis. Issue 2 (March 2015) - Hasnain, Seyed E.; O'Toole, Ronan F.; Grover, Sonam; Ehtesham, Nasreen Z.
Summary Whole Genome Sequencing (WGS) is emerging as a very powerful tool for the management, outbreak analyses, surveillance and determining drug resistance of human infectious pathogens including Mycobacterium tuberculosis and MRSA. WGS can also discriminate relapse TB from re-infection and the resolution provided by WGS has no comparison to conventional technologies. With current cost coming down to <£70 per bacterial genome, WGS has emerged as an alternative to all the existing technologies put together. We discuss the advantage and disadvantages of WGS and whether it can become a point of care tool in not just developed countries but also in developing countries which have a huge TB burden. The likely utility of WGS for other pathogens and also in characterizing holobionts is also discussed.